A Comprehensive Review and Analysis of Solar Photovoltaic Array Configurations under Partial Shaded Conditions. (8th March 2012) - Ramaprabha, R.; Mathur, B. L.
Abstract : The aim of this paper is to investigate the effects of partial shading on energy output of different Solar Photovoltaic Array (SPVA) configurations and to mitigate the losses faced in Solar Photovoltaic (SPV) systems by incorporating bypass diodes. Owing to the practical difficulty of conducting experiments on varied array sizes, a generalized MATLAB M-code has been developed for any required array size, configuration, shading patterns, and number of bypass diodes. The proposed model which also includes the insolation-dependent shunt resistance can provide sufficient degree of precision without increasing the computational effort. All the configurations have been analyzed and comparative study is made for different random shading patterns to determine the configuration less susceptible to power losses under partial shading. Inferences have been drawn by testing several shading scenarios.